Study of Science Process Skills in Lesson Plan by Prospective Biology Teachers Based on Merdeka Curriculum - Maesaroh Maesaroh; Eka Kartikawati; Mega Elvianasti; Irdalisa Irdalisa; Susanti Murwitaningsih (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of learning planning is to ensure that instruction is organised and carried out in a way that achieves the aims of the curriculum. Before settling on the Merdeka Curriculum, the Indonesian school system went through at least eleven curricula. An essential skill for any educator is the ability to craft lessons that meet the requirements of the curriculum at any given time. This study uses a quantitative descriptive method using data from learning plan documents made by prospective biology teachers and analyzed by researchers based on the emergence of science process skills. The analysis process also uses the National Education Standard document on Merdeka Curriculum. The results of this study are: 1) lesson plans made based on the curriculum before K13 and the Merdeka Curriculum had around 8-15 pages, while the lesson plans based on the revised 2013 curriculum and the Merdeka curriculum were 1-1.5 pages. The material and evaluation of learning in the lesson plans for the revised K13 and the Merdeka Curriculum are provided using links or barcodes. 2) the discovery of process skills indicators in the form of basic process abilities and the ability to integrate processes into learning objectives. 3) lecture methods, online learning resources, and multiple choice questions are the most widely used in lesson plans. In the lesson plans analyzed, there has not been an explicit finding of product or project-based learning activities characteristic of the Merdeka Curriculum's learning process.